2022
DOI: 10.1108/sjme-03-2022-0043
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of purchase intention in Instagram Commerce

Abstract: Purpose This study aims to analyze the factors that drive purchases via Instagram and contribute to the growth of Instagram Commerce and examine the moderating role of gender, age and experience in Instagram use in the proposed relationship between six variables derived from commitment–trust theory, the technology acceptance model and consumer decision-making theory. Design/methodology/approach A survey was completed by respondents after watching a video about Instagram Commerce. A total of 404 valid response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 65 publications
4
19
1
1
Order By: Relevance
“…The improvement of attitude increases the intention to buy agricultural produce from SFSCs using social commerce. This result is similar to those of previous research into consumer use of Instagram (Herzallah et al, 2022), Facebook (Suraworachet et al, 2012), WeChat (Bilal et al, 2022), and consumer online buying groups (Lin and Wu, 2015). Perceived behavioral control is a predictor of purchase intention in social commerce SFSCs, which aligns with previous research on social commerce (Lin and Wu, 2015;Smith et al, 2013) and SFSCs (Giampietri et al, 2018).…”
Section: Discussionsupporting
confidence: 89%
“…The improvement of attitude increases the intention to buy agricultural produce from SFSCs using social commerce. This result is similar to those of previous research into consumer use of Instagram (Herzallah et al, 2022), Facebook (Suraworachet et al, 2012), WeChat (Bilal et al, 2022), and consumer online buying groups (Lin and Wu, 2015). Perceived behavioral control is a predictor of purchase intention in social commerce SFSCs, which aligns with previous research on social commerce (Lin and Wu, 2015;Smith et al, 2013) and SFSCs (Giampietri et al, 2018).…”
Section: Discussionsupporting
confidence: 89%
“…Chen et al (2009) argue that perceived usefulness is the most influential determinant of continuance usage intention when exploring continuance intention of customers based on their IT-related capabilities, social cognitive factors, and performance. In the Technology Acceptance Model framework, perceived usefulness is instrumental to explaining Behavioural Intention to use technology (Herzallah et al, 2022;Saheb et al, 2022;Liébana-Cabanillas et al, 2022). In this regard, past studies have shown a positive relationship between perceived usefulness and continuance intention in different contexts such as mobile apps (Huang & Ren, 2020), mobile payment (Liébana-Cabanillas et al, 2015b), and online learning (Lin & Wang, 2012).…”
Section: 310mentioning
confidence: 99%
“…Previous studies have shown that age affects intention (Na et al, 2021;Watanabe et al, 2021;Herzallah et al, 2022); and in this study, age was included as a control variable (Hien et al, 2021;Klaver et al, 2021;Saari et al, 2021). Research on the moderating role of COVID-19 fear in the relationship between satisfaction and travel intention is lacking; therefore, this study proposes the seventh hypothesis: H7.…”
Section: The Moderating Role Of Fear Of Covid-19mentioning
confidence: 87%